A formação de professores da Primeira República no Pará (1900-1904) - COSTA, Rafaela Paiva (Universidade Federal do Pará, 2012)
This work is about Education in the First Republic (1889-1930) and, as main issue, the official model for Teacher Education in the early twentieth century in Para, specifically, between 1900 and 1904. Was investigated the monthly periodical "School: official journal of education in the state of Para", through which we scrutinize the ideal of" good teacher " desired by the Republican regime, its theoretical influences and socio-political aims. For this, we work with the conceptual notions of Symbolic Domination, Habitus, Field and Capital of Pierre Bourdieu, as well as the concept of social representation of Roger Chartier. Overall, we identified the understanding of teaching as "priesthood" that the discussions were guided by international and national elite thinking were reflected in the educational field and that this formation of the "masters" intended to consolidate the Republic, through the instruction of a moral and civic content.